Time-Course Transcriptome Analysis of Lungs From Mice Infected With Hypervirulent Klebsiella pneumoniae via Aerosolized Intratracheal Inoculation - Zheng, Xinying; Guo, Jianshu; Cao, Chaoyue; Qin, Tongtong; Zhao, Yue; Song, Xiaolin; Lv, Meng; Hu, Lingfei; Zhang, Lili; Zhou, Dongsheng; Fang, Tongyu; Yang, Wenhui (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Hypervirulent Klebsiella pneumoniae (hvKp) can cause life-threatening community-acquired infections among healthy young individuals and is thus of concern for global dissemination. In this study, a mouse model of acute primary hvKp pneumonia was established using aerosolized intratracheal (i.t.) inoculation. Subsequently, the time-course transcriptional profile was created of the lungs from the mouse model at 0, 12, 24, 48 and 60 hours post-infection (hpi) using RNA Sequencing (RNA-Seq). RNA-Seq data were analyzed with the use of differential expression analysis (DEGs), time-series gene clustering, weighted gene co-expression network analysis (WGCNA) and CIBERSORT. A gradual change in the transcriptional profile of the lungs was observed and reflected expected disease progression. At 12 hpi, genes related to acute phase inflammatory response increased in expression and lipid metabolism appears to have a pro-inflammatory effect. At 24 hpi, exacerbation of inflammation was observed and active IFN-γ suggested that signaling promoted activation and recruitment of lung immune cells, including natural killer (NK) cells and macrophages, occurred. Genes related to the maintenance of the structural integrity of lung tissues showed a sustained decrease in expression after infection and the decrease was especially significant at 48 hpi. TNF, IL-17, MAPK and NF-kB signaling pathways may play key roles in the immunopathogenesis mechanism at all stages of infection. Saa1, Aoah, Irak3, Lcn2 and Slpi were all significantly upregulated during infection. Saa1, Aoah and Irak3 are associated with the cell wall component lipopolysaccharide (LPS) of Gram-negative bacteria that causes host inflammatory response. The rarely studied Lcn2 and Slpi encode antimicrobial proteins and could be important targets for subsequent studies of hvKp pulmonary infection. To our knowledge, this paper represents the first study to investigate the pulmonary transcriptional response to hvKp infection. The results provide new insights into the molecular mechanisms underlying the pathogenesis of hvKp pulmonary infection that can contribute to the development of therapies to reduce hvKp pneumonia.